Different Activation of TRAF4 and TRAF6 in Inflammatory Bowel Disease - Jun Shen; Yuqi Qiao; Zhihua Ran; Tianrong Wang (Hindawi Limited, 2013)
In recent years, interests combining the exploration of tumor necrosis factor receptor-associated factor 4 (TRAF4) and TRAF6 in immune cells and transgenic mice are emerging. Although it has been found that TRAF4 and TRAF6 share the same TRAF binding sites, comprehensive study of TRAF4 and TRAF6 in inflammatory bowel disease (IBD) is still lacking. This paper shows similar and different expression patterns of TRAF4 and TRAF6 in patients with IBD. The results indicate that TRAF4 and TRAF6 are overexpressed in IBD. TRAF4 and TRAF6 play different roles in the pathogenesis of IBD. Moreover, TRAF4 may be an indicator of endoscopic disease activity of UC and TRAF6 preactivation can be detected in noninflamed colonic segments.